2003
DOI: 10.1200/jco.2003.05.185
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Trial of Weekly Combretastatin A4 Phosphate: Clinical and Pharmacokinetic Results

Abstract: CA4P was well tolerated in 14 of 16 patients at 52 or 68 mg/m2; these are doses at which tumor blood flow reduction has been recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
247
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(260 citation statements)
references
References 16 publications
10
247
2
1
Order By: Relevance
“…In the first study by Rustin et al (2003a) CA4P was given weekly for 3 weeks followed by a week gap . Thirty-four patients with advanced solid tumours received 167 infusions.…”
Section: Combretastatin A4 Phosphatementioning
confidence: 99%
“…In the first study by Rustin et al (2003a) CA4P was given weekly for 3 weeks followed by a week gap . Thirty-four patients with advanced solid tumours received 167 infusions.…”
Section: Combretastatin A4 Phosphatementioning
confidence: 99%
“…Phase I human cancer clinical trials of the sodium CA4 phosphate prodrug (2; Fig. 1) have been successfully completed (12,13) and the drug is currently undergoing phase II trials.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast enhanced (DCE) MRI based on the transport properties of the small paramagnetic contrast agent gadolinium-DTPA (Gd-DTPA) is the most commonly used imaging approach to study tumor vascular perfusion and permeability. DCE MRI was included as part of the Phase I clinical trials of CA4P (24,25). Results of preclinical and clinical DCE MRI studies have shown a reversible change in vascular perfusion in the tumor periphery following a single dose of VTA (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%